Newcomers foray reflects Puteri Umno resolves for change - New Sabah Times English, (KK) (New Sabah Times English (KK), 2013)
KUALA LUMPUR: The large number of candidates entering the fray in Puteri Umno polls next month is a manifestation of the wing resolves for transformation.